Evaluating the effect of mental health curriculum on secondary school students’ mental health literacy and knowledge and attitude to mental illness - Batool Zeidabadi; Mahsa Khodayarian; Reza Sadeghi; Sara Jambarsang (Scientific Reports, 2025)
Abstract Enhancing the mental health literacy of students stands out as a crucial factor in mitigating social harm within society. This randomized controlled trial assessed the effectiveness of a mental health literacy program called the “Mental Health and High School Curriculum Guide,” consisting of six modules (1) Understanding mental health and mental illness, (2) Stigma of mental illness, (3) Information about specific mental illnesses, (4) experiences of mental illness, (5) seeking and receiving support, and (6) the importance of positive mental health. Which was introduced in the first secondary schools in the southeastern region of Iran in 2023. There were 40 teachers and 562 students from 20 schools involved in the study and randomly divided in two groups of intervention and control groups. The levels of mental health literacy, knowledge, and attitudes towards mental illness were measured using a questionnaire in two control and intervention groups, both before and after the mental health curriculum was implemented. A two-day training workshop was initially conducted for the intervention group teachers to familiarize them with the mental health curriculum. Following this preparation, the teachers introduced and implemented the mental health literacy curriculum in their classrooms for the students. The results of the study showed that the intervention group showed notable improvements in mental health literacy, with mean scores rising from 81 ± 6.80 to 98 ± 9.23, while the control group had no significant change (p < 0.001). Similar significant gains were observed in mental health knowledge and attitudes (p < 0.001). Mental health knowledge scores increased from 11.12 ± 4.31 to 18.42 ± 3.28, and scores on mental disorders improved from 19.76 ± 5.26 to 22.60 ± 3.83, with no significant changes in the control group (p < 0.001). Also, the results showed that after adjusting the influencing factors (gender, teacher, number of children in the family), mental health literacy (p < 0.001), mental health knowledge (p < 0.001), attitude to mental illness/disorders (p < 0.002) had a significant effect. The study revealed that students’ mental health literacy, knowledge and attitudes were positively impacted by the classroom program.